(untitled) (Research, Society and Development, 2021)
An alternative to teaching biological evolution, and in particular human evolution, is the use of cinema in classroom, both to illustrate a certain conceptual content, how much to instrumentalize the students in the audiovisual production process in which multiple skills are required until the completion of this imagery resource. In order to investigate the construction of knowledge about evolutionary biology and human evolution in audiovisual productions of undergraduate students of the Biological Sciences course of a Brazilian public university, ten productions were selected with themes related to human evolution for which elements of the grammar of cinema were analyzed, especially the cinematographic plans and their unfolding in the generation of meaning from a semiotic analysis inspired by Peirce. Most of the productions presented a predominance of closed plans, which indicates an approximation with the scientific discourse and most of the concepts used by the students approached the scientific construction on evolution. The results obtained here also indicate that the use of these videos as a didactic resource is possible, since they present characteristics necessary to a film with pedagogical intentions.